Plato's Gorgias: Speech, Soul and Politics - Machek, David; Mikeš, Vladimír (Brill's Plato Studies Series, 2024)
In the Gorgias Plato offers a synthesis of what he thinks about the bitter conflict between philosophical and non-philosophical approaches to one's responsibilities in private and public life. This book contributes to a deeper understanding of this historically and conceptually rich canvas by shedding light on its main topics: speech in its philosophical and non-philosophical forms, psychology in relation to virtuous life, and politics which charges the two former topics with high stakes that call for personal choices.